1999
DOI: 10.1046/j.1365-2036.1999.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rabeprazole, a new proton pump inhibitor, in triple therapy for Helicobacter pylori infection—comparison with omeprazole and lansoprazole

Abstract: INTRODUCTIONSince the signi®cant impact of Helicobacter pylori infection in the development of most gastric diseases has been established, curative therapy for the infection has been of growing clinical interest. A recent trend in curative therapy is the so-called triple therapy, 1 which consists of a proton pump inhibitor (PPI) and two different antimicrobials. Various regimens of triple therapy have been reported that utilize different combinations of proton pump inhibitor or antimicrobials, with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 27 publications
7
81
1
1
Order By: Relevance
“…[12][13][14][15] In terms of H. pylori eradication, the effectiveness of rabeprazole-based triple therapy has been shown in patients with chronic gastritis, peptic ulcer disease and non-ulcer dyspepsia. [16][17][18][19][20] The present study was designed to determine whether rabeprazole, in combination with clarithromycin and either amoxicillin or metronidazole, is therapeutically equivalent to the same omeprazole-based regimens in the eradication of H. pylori in subjects with documented peptic ulcer disease and H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] In terms of H. pylori eradication, the effectiveness of rabeprazole-based triple therapy has been shown in patients with chronic gastritis, peptic ulcer disease and non-ulcer dyspepsia. [16][17][18][19][20] The present study was designed to determine whether rabeprazole, in combination with clarithromycin and either amoxicillin or metronidazole, is therapeutically equivalent to the same omeprazole-based regimens in the eradication of H. pylori in subjects with documented peptic ulcer disease and H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…RPZ-based eradication therapies 7,[25][26][27] as the first-line therapy. Similar eradication rates have been reported for triple therapies using RPZ as for those with omeprazole (OPZ) and lansoprazole (LPZ) .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Triple therapy comprising a proton pump inhibitor (PPI) and two antibiotics yields high eradication rates ranging from 80% to 95% but not 100%. [4][5][6][7] With the increased use of H. pylori eradication treatments, the overall number of cases of failed eradication has increased. It has been reported that ranitidinebismuth-based triple therapies 8,9 and quadruple therapies [PPI + bismuth + metronidazole (MNZ) + tetracycline] [10][11][12] are the most effective second-line therapies in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the rate of eradication by triple therapy ranges from 80% to 95% (Miwa, Ohkura et al, 1999). Many studies have reported that there are no significant differences in the rate of eradication when any of the 3 agents, omeprazole (OPZ), lansoprazole (LPZ), and rabeprazole (RPZ), ANNALS OF Cancer Research and Therapy is used as a PPI (Miwa, Ohkura et al, 1999;Inaba, Mizuno et al,2002) however, reported that RPZ achieved a higher rate of eradication than LPZ. In addition, several studies have indicated that there are no significant differences in the rate of eradication among different doses of RPZ as a PPI, 10mg, 20mg, and 40mg (Hokari, Sugiyama et al, 2001;Miwa, Yamada et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The eradication regimen consists of triple therapy with a proton pump inhibitor (PPI), amoxicillin (AMPC), and clarithromycin (CAM) [PPI/AC]. In Japan, the rate of eradication by triple therapy ranges from 80% to 95% (Miwa, Ohkura et al, 1999). Many studies have reported that there are no significant differences in the rate of eradication when any of the 3 agents, omeprazole (OPZ), lansoprazole (LPZ), and rabeprazole (RPZ), ANNALS OF Cancer Research and Therapy is used as a PPI (Miwa, Ohkura et al, 1999;Inaba, Mizuno et al,2002) however, reported that RPZ achieved a higher rate of eradication than LPZ.…”
Section: Introductionmentioning
confidence: 99%